Individual and organizational factors associated with public health workforce competencies to advance health equity. - Paula M Kett; Shahida Shahrir; Betty Bekemeier; Kay Schaffer; Danielle J Zemmel; Davis G Patterson (PLOS Global Public Health)
Little is known about how to develop public health workforce capacity for health equity work. We explored associations of individual and organizational characteristics of local public health departments (LHDs) with competencies essential for advancing health equity. Data included responses of 29,751 staff from 742 LHDs in 48 states to the 2021 Public Health Workforce Interests and Needs Survey, plus LHD characteristics and county demographics. Logistic regression assessed associations between key factors and staff-reported "knowledge of" and "confidence in addressing" structural racism, health equity, social determinants of equity (SDoE), social determinants of health (SDOH), and environmental justice, as well as belief and involvement in addressing racism through one's work. Staff with a master's degree or higher compared to others had greater odds of reporting confidence in addressing structural racism (adjusted odds ratio [AOR] = 1.23) and health equity (AOR = 1.56), agreeing that addressing racism should be a part of their work (AOR = 2.45) and being involved in such efforts (AOR = 1.57). Staff identifying as Black, compared to white, had greater odds of reporting confidence in addressing all concepts: structural racism (AOR = 1.98), health equity (AOR = 1.34), SDoE (AOR = 1.53), SDOH (AOR = 1.21), and environmental justice (AOR = 1.72) and agreeing that addressing racism should be a part of their work (AOR = 2.11). Patterns were similar among staff identifying as Hispanic/Latino and other persons of color. Black (AOR = 0.68) and Hispanic/Latino (AOR = 0.83) staff had lower odds, however, of reporting engagement in activities to address racism. Finally, competencies positively associated with nearly all outcomes included cross-sector collaboration, ability to incorporate health equity into programming, and policy advocacy. LHD workforce development should include training that involves explicitly naming structural racism's effects and complementary skills, such as policy development and cross-sector partnership building. Further exploration is needed into how best to grow commitment among white staff and to support staff of color in health equity work.